Evaluation of PROMIS Preference Scoring System (PROPr) in Patients Undergoing Hemodialysis or Kidney Transplant. Issue 9 (September 2021) - Zhang, Jing; Dewitt, Barry; Tang, Evan; Breitner, Daniel; Saqib, Mohammed; Li, Dan; Siddiqui, Rabail; Edwards, Nathaniel; Peipert, John Devin; Hays, Ron D.; Hanmer, Janel; Mucsi, Istvan
Visual Abstract: Abstract : Background and Objectives: A preference-based health utility score (PROPr) can be calculated using Patient-Reported Outcomes Measurement Information System domain scores. We assessed the construct validity of PROPr among patients treated with KRT (hemodialysis or kidney transplant). Design, setting, participants, & measurements: We performed a secondary analysis of data collected in multicenter, cross-sectional studies of adults treated with KRT, recruited between April 2016 to March 2020 in Toronto, Canada. All participants provided informed consent. The outcome was the PROPr score. Coadministered outcome variables included the Short-Form Six-Domain (SF-6D) and EuroQol Five-Domain Five-Level (EQ-5D-5L) scores. Socioeconomic and clinical variables included age, sex, diabetes, eGFR, serum albumin, hemoglobin, KRT, and Charlson Comorbidity Index. Construct validity was assessed through correlations between PROPr and SF-6D or EQ-5D-5L, and associations between PROPr and other exposure variables. Health-condition impact estimates (coefficients for health conditions compared with a referent category, e.g., dialysis versus kidney transplant) were calculated using multivariable linear regression. Results: The mean (SD) age of the 524 participants was 57 (17) years, 58% were male, and 45% were White. Median (interquartile range) score was 0.39 (0.24–0.58) for PROPr, 0.69 (0.58–0.86) for SF-6D, and 0.85 (0.70–0.91) for EQ-5D-5L. Large correlations were observed between PROPr versus SF-6D (0.79; 95% confidence interval [95% CI], 0.76 to 0.82) and EQ-5D-5L (0.71; 95% CI, 0.66 to 0.75). Both PROPr and the other utility indices demonstrated health-condition impact in the expected direction. For example, the estimate for PROPr was −0.17 (95% CI, −0.13 to −0.21) for dialysis (versus kidney transplant), −0.05 (95% CI, −0.11 to 0.01; P =0.08) for kidney transplant recipients with an eGFR of <45 versus ≥45 ml/min per 1.73 m 2, and −0.28 (95% CI, −0.22 to −0.33) for moderate/severe versus no/mild depressive symptoms. Conclusions: Our results support the validity of PROPr among patients treated with KRT.